Pharmacy Student Recommendations on Self-Medication for Headaches: A Cross-Sectional Study in Surabaya - Halim, Steven Victoria; Pratama, Jeffry Refananto; Karinda, Itsna Laudzy; Setiadi, Adji Prayitno; Aditama, Lisa; Wibowo, Yosi Irawati; Brata, Cecilia; Setiawan, Eko (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Assessing students’ ability to provide appropriate recommendations for self-medication requests is key in developing course materials for future pharmacists. Until recently, the number of published articles evaluating the appropriateness of recommendation provided by pharmacy students towards headache cases, as one of the most common symptoms urging people to seek advice from professional healthcare, is still limited. This observational study with cross-sectional design aims to identify the type and appropriateness of recommendation given by pharmacy professional degree students on two types of headache cases, i.e., tension type headache and migraine due to adverse drug reaction (ADR). The students characteristic data, type, and recommendation appropriateness were analyzed descriptively. In total, 86 students were involved in this research (response rate 82.7%) with different recommendation profiles for two different headache cases. The majority of the participants recommended a pharmaceutical product for tension type headache while referral to physicians was advised for migraine due to ADR. The appropriateness analysis findings revealed that students gave more appropriate recommendations for tension type headache (89.5%) compared to migraine due to ADR (77.9%) case. Therefore, students’ ability to provide relevant recommendations for headaches due to ADR requires further improvement by giving some cases accordingly during the learning process.